Hate Speech on Social Media in the Axis of Islamophobia: Example of TikTok - Mustafa Böyük (Medya ve Din Araştırmaları Dergisi)
This study focuses on the detection and analysis of Islamophobic hate speech on the TikTok platform. Social media platforms have a great impact in terms of reaching masses and sharing information. However, these platforms can also pave the way for the spread of negative content such as hate speech and discrimination. TikTok draws attention with its short video format, which is especially popular among young people. For this reason, it offers an important area of investigation in terms of the spread of hate speech and discrimination content. In this study, posts containing Islamophobic hate speech on TikTok were identified through the keywords ‘Islam’, ‘Muslim’, ‘Terrorist’, ‘Jihad’, ‘Sharia’, ‘Radical Islam’ and ‘Islamist’. These keywords were chosen from the terms that commonly define Islamophobic discourse in the literature. The 10 TikTok posts selected using simple random sampling technique were analysed by critical discourse analysis method. Critical discourse analysis is a method that analyses how texts and speeches gain meaning in the social context and how these meanings reflect social power relations. In the study, linguistic and visual analyses of Islamophobic content on TikTok were conducted. The research was conducted in the first six months of 2024. The data collection process carried out during this period was obtained as a result of the scans carried out on TikTok using the keywords mentioned above. The results of the study show that Islamophobic hate speech is spread linguistically and discursively through posts on TikTok. Islamophobic content reinforces negative stereotypes against Muslims and damages social cohesion. Such content leads to marginalisation, exclusion and violence against Muslims. Islamophobia and hate speech increase social polarisation and create distrust and hostility in society.